2021
DOI: 10.1111/ddg.14451
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis is associated with fissured tongue but not geographic tongue: a prospective, cross‐sectional, case‐control study

Abstract: Summary Background and objectives It has been postulated that psoriasis is associated with tongue lesions and geographic tongue might be “oral psoriasis”. However, reports are inconclusive, prevalence rates vary and data for Europe are sparse. In this prospective case‐control study we investigated the point‐prevalence of tongue conditions in an Austrian cohort. Patients and methods Psoriasis patients and healthy volunteers were assessed regarding tongue and skin lesions, age, sex, smoking habits, allergies, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The PASI score was statistically higher in patients affected by GT, and exhibited less improvement after treatment (204). However a prospective case-control study in an Austrian cohort found that psoriasis was associated with fissured tongue but not with GT (207), and the severity of the disease evaluated by the PASI scale did not influence mucosal involvement (208).…”
Section: Oral Comorbidities Geographic Tonguementioning
confidence: 94%
“…The PASI score was statistically higher in patients affected by GT, and exhibited less improvement after treatment (204). However a prospective case-control study in an Austrian cohort found that psoriasis was associated with fissured tongue but not with GT (207), and the severity of the disease evaluated by the PASI scale did not influence mucosal involvement (208).…”
Section: Oral Comorbidities Geographic Tonguementioning
confidence: 94%
“…Different factors are associated with these two patterns (Dafar et al, 2016 ). The geographic tongue is characterized by the loss of filiform papillae and by habitual factors, for example chewing tobacco (Assimakopoulos et al, 2002 ; Dafar et al, 2016 ); the genesis of fissures is unknown, discussing genetic factors and systemic diseases (Dawson, 1974 ; Eidelman et al, 1976 ; Guggenheimer et al, 2000 ; Hamrah et al, 2021 ; Marcoval et al, 2012 ; Monshi et al, 2021 ). The papillae in fissured tongues are preserved and the tongue shows a higher accumulation of inflammatory cells (Kullaa‐Mikkonen & Sorvari, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Seither erschienen in dieser Zeitschrift Publikationen zur Psoriasis in dreistelliger Zahl. In jüngster Zeit umspannen die Themen grundlegende pathophysiologische Aspekte, [3][4][5] therapeutische Ansätze, [6][7][8][9][10][11] epidemiologische Fragen, 12 diagnostische und klinische Entwicklungen, [13][14][15] psychosoziale Aspekte, [16][17][18] bis hin zu Versorgungsforschung und Registerstudien. [19][20][21][22] Empfehlungen zur praktischen Umsetzung neuer Erkenntnisse kulminieren schließlich in Leitlinien.…”
Section: Wo Stehen Wir?unclassified